2021
DOI: 10.3389/fphar.2021.714287
|View full text |Cite|
|
Sign up to set email alerts
|

The Therapeutic Principle of Combined Strengthening Qi and Eliminating Pathogens in Treating Middle-Advanced Primary Liver Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: The combination of strengthening Qi and eliminating pathogens is an available therapeutic principle in traditional Chinese medicine (TCM) for primary liver cancer (PLC) at middle-advanced stage. However, there is a lack of reasonable evidence to support the proper application of this therapeutic principle. This meta-analysis aims to evaluate the efficacy and safety of Chinese medicinal formulas (CMFs), including two subgroup analyses of the principle of strengthening Qi and eliminating pathogens.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The effect of herbal medicine on gastrointestinal symptoms is often meta-analyzed (see Table 5 ). The included meta-analyses showed significant negative effects of herbal medicine on the incidence of nausea and vomiting and diarrhea [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Inappetence was significantly relieved in patients with primary liver cancer using Chinese medicinal formulas [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of herbal medicine on gastrointestinal symptoms is often meta-analyzed (see Table 5 ). The included meta-analyses showed significant negative effects of herbal medicine on the incidence of nausea and vomiting and diarrhea [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Inappetence was significantly relieved in patients with primary liver cancer using Chinese medicinal formulas [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included meta-analyses showed significant negative effects of herbal medicine on the incidence of nausea and vomiting and diarrhea [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Inappetence was significantly relieved in patients with primary liver cancer using Chinese medicinal formulas [ 57 ]. In patients with colorectal cancer, anorexia , constipation and abdominal pain were not found to be significantly alleviated by the use of traditional herbal medicines, but abdominal distension was [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…to achieve maximal efficacy in cancer therapy with minimal adverse reactions ( 57 ). Numerous studies have described the clinical efficacy and safety of TMPs for colorectal cancer ( 58 ), non-small cell lung cancer ( 59 ), and liver cancer ( 60 ), as well as for some cancer-related symptoms such as insomnia ( 61 ), pain ( 62 ), and anemia ( 63 ). Thus, mining TMPs with scientific and systematic methods can serve as an important strategy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Traditional Chinese Medicine (TCM) has been extensively adopted as a pool filed with numerous new therapeutic agents due to its beneficial effects, accessible availability, and restricted adverse effects. Notably, it has found that Chinese medicinal formulas (CMFs) could be beneficial to HCC patients with approximately 1–2-years survival time [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%